Digital transformation and knowledge management in the public sector - Alvarenga, A.; Matos, F.; Godina, R.; Matias, J. (Sustainability, 2020)
Digitizing public services is, at the moment, an essential necessity for numerous governments around the world. An improved government through digitization will not only have a growing effect on businesses, but it will also be able to intensify citizen engagement and push for economic growth. During the last 10 years more countries have progressively begun to provide digital services to their citizens. Therefore, in order to address this development, the purpose of this paper is to analyze the evolution of the digital government literature in order to describe the aspects of digital transformation in the public sector and how it is related to knowledge management. In this study the methodology is quantitative and it is based on a review and a survey made with the main goal being the estimation from several collected data on how the digital transformation process in the Public Administration takes place and what its relationship is with knowledge management. The review study is based on articles found on Scopus database and it addresses the role that digital government research plays in the theory and practice of knowledge management. In the survey study, 54 employees working for the services of the two governmental areas of the Portuguese Ministry of the Environment were surveyed. The results show that the research on the theme is still at an exploratory stage due to the lack of studies relating digital government to knowledge management effectiveness in the public sector. The results also show that the success of digital government seems to be related with the quality of the organizations' knowledge management, complementing each other for significant improvements in the public sector. In terms of originality, this study aims to contribute and stimulate data-driven discussions regarding the impacts of the digital transformation in the public sector and their relation with the implementation of knowledge management practices. The results offer insights into future research needs.